هۆكاری لاوازییەکانى کارامەیى دەربڕین و داڕشتن لاى خوێندكارانی زانكۆ بەپێى تێڕوانینى مامۆستایان - سعید, ریگر محمد سلیم (Sulaimani Journal for Humanities, 2021)
The skill of expression and composition is a linguistic activity, to express their feelings orally or in writing, in which individuals talk about their feelings and feelings in a functional way, and their skills and self-confidence develop their abilities to choose and organize ideas. Despite the great importance of students’ expression and composition to achieve their goals, many studies have confirmed that poor expression and construction hinder students from achieving the goals they are trying to achieve. Determining the purpose of this research includes the study sample of teachers in the Kurdish Language Department at the College of Basic Education, the researcher prepared a preliminary sample for the diagnosis of the causes of weakness and skills in expression and composition using the main survey and presented it consisting of teachers. The researcher achieved several goals. He used many Kurdish and Arabic sources and then presented some results, suggestions and conclusions